Analysis Of Personal Financial Planning Strategies Of Salaried Class Using Analysis Of Variance Method: A Case Of Dehradun City In Uttarakhand (India) - Pandey, Dinesh Chandra; Bohra, Dr. N S; Garg, Shobhit (The journal of contemporary issues in business and government, 2021)
After the liberalization of the Indian economy in 1992, the wave of globalization benefitted Indian Financial services and individuals. However, Tier-II cities of India participated in this rally by the final part of the decade. Financial literacy is an important aspect in making a well-informed decision in the highly dynamic and convoluted market. Financial crisis can be attenuated under Financial literacy. In the current era of automation, the convoluted global economy increases the risk spectrum of the individual. Keeping in mind the large population of India works in the shambolic sector with minimum social security. As the Government withdrew pension schemes from government jobs, financial security will be a huge concern for our population. Personnel financial management will be effective as well as efficient if only financial literacy is acquired by individuals. Personal Financial management includes financial literacy and Household saving patterns of individuals. In this study, we try to identify and analyze the level of financial literacy and its relationship with the demographic profile of the salaried class and analyze the household saving pattern of the salaried class of Tier II city. Analysis of variance method used for establishing the relationship between financial literacy and demographic profile of the sample. The findings of the study imply that Financial literacy is independent of age and monthly income but not independent from family responsibility. The finding also suggests a change in household saving patterns as the age of individuals increases. This study would help in adopting appropriate strategies to improve the level of personal financial management for individuals.